2009
DOI: 10.1159/000219953
|View full text |Cite
|
Sign up to set email alerts
|

Objective Acoustic-Phonetic Speech Analysis in Patients Treated for Oral or Oropharyngeal Cancer

Abstract: Objective: Speech impairment often occurs in patients after treatment for head and neck cancer. New treatment modalities such as surgical reconstruction or (chemo)radiation techniques aim at sparing anatomical structures that are correlated with speech and swallowing. In randomized trials investigating efficacy of various treatment modalities or speech rehabilitation, objective speech analysis techniques may add to improve speech outcome assessment. The goal of the present study is to investigate the role of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…It was reported that vowel working space has positive relationship with speech intelligibility 10,20-22. Vowel working space means the space enclosed by the first two formants of corner vowels 22.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that vowel working space has positive relationship with speech intelligibility 10,20-22. Vowel working space means the space enclosed by the first two formants of corner vowels 22.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 22 studies, 10 include more than 20 patients, and also 10 include between 2 and 18 subjects . Two articles do not report the number of subjects involved in the acoustic analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (27%) include both patients treated for cancer of the oral cavity and patients treated for oropharynx cancer …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, until recently, the latter were usually restricted to voice quality measurements on sustained vowels or single phones, i.e. speech stimuli that differ considerably from natural speech encountered in realistic communication settings [3][4][5][6] . Important speech criteria, such as intelligibility, cannot be obtained in this way and require much more elaborate solutions.…”
Section: Introductionmentioning
confidence: 99%